Economic viability of arctic shipping under IMO environmental regulations: a well-to-wake assessment of different carbon tax scenarios - Miao, Hongzhi; Feng, Xinyuan; Li, Xinwei (Frontiers in Marine Science, 2025)
The accelerated melting of Arctic sea ice has established the Northern Sea Route (NSR) as an emerging alternative for international shipping. However, increased maritime activities pose significant environmental risks to this sensitive region. This study evaluates the economic implications of the International Maritime Organization (IMO) environmental regulations on Arctic shipping through a well-to-wake assessment framework. Using a multi-scenario economic analysis model, we compare transportation costs between the NSR and the traditional Suez Canal Route (SCR) under various IMO environmental policy scenarios. Our findings reveal: (1) Without carbon taxation, the NSR generally offers lower unit transportation costs than the SCR. However, the IMO’s prohibition of heavy fuel oil (HFO) in Arctic waters creates a 12-15% cost advantage for vessels using HFO on the SCR compared to those using clean fuels on the NSR. (2) However, the IMO’s prohibition of heavy fuel oil (HFO) in Arctic waters creates a 12-15% cost advantage for vessels using HFO on the SCR compared to those using clean fuels on the NSR. (3) In unilateral carbon tax scenarios, the NSR consistently remains less economically viable than the SCR using HFO, primarily due to mandatory clean fuel requirements in Arctic waters. (4) The environmental benefits of LNG propulsion demonstrate considerable technological sensitivity, with life-cycle emission reduction efficiency heavily dependent on engine selection and methane slip mitigation. Our analysis indicates that current Arctic environmental regulations lack policy coordination. To simultaneously achieve ecological protection and economic viability, we recommend implementing a dynamic carbon tax threshold mechanism linked to clean fuel technology standards.